Effect of Economic Value Added, Market Value Added, Earning per Share and Net Profit Margin on Stock Returns in Metal Companies Listed on the Indonesia Stock Exchange: Pengaruh Economic Value Added, Market Value Added, Earning per Share dan Net Profit Margin Terhadap Return Saham pada perusahaan logam Yang Terdaftar Di Bursa Efek Indonesia - Silvia Handayani; Sriyono Sriyono (Academia Open, 2021)
This study aims to determine the effect of Economic Value Added (EVA), Market Value Added (MVA), Earning Per Share (EPS) and Net Profit Margin (NPM) on Stock Returns in metal sub-sector companies listed on the Indonesia Stock Exchange (IDX). . The research method uses a quantitative approach. Data analysis used a regression model with Eviews 9 software. The sample of this study was 49 metal sub-sector companies listed on the IDX in 2013-2019. The results showed that Economic Value Added, Market Value Added, Earning Per Share, and Net Profit Margin together had no effect on stock returns. Partially Economic Value Added has no effect on stock returns, Market Value Added has a significant and positive effect on stock returns, Earning Per Share has no effect on stock returns, and Net Profit Margin has no effect on stock returns.